2020
DOI: 10.1093/eurjpc/zwaa074
|View full text |Cite
|
Sign up to set email alerts
|

Novel antidiabetic drugs and risk of cardiovascular events in patients without baseline metformin use: a meta-analysis

Abstract: Aims To evaluate the effect of sodium-glucose cotransporter-2 (SGLT-2) inhibitors and glucagon-like peptide-1 receptor agonists (GLP-1RAs) on major cardiovascular events (MACE) in metformin-naïve patients with type 2 diabetes (T2D). Methods and results A meta-analysis was performed of randomized controlled clinical trials of GLP-1RAs and SGLT-2 inhibitors on T2D populations, after searching the PubMed/MEDLINE, Embase, and Coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
0
22
0
1
Order By: Relevance
“…A meta-analysis on SGLT2 inhibitors also showed a consistent reduction in the risk of cardiovascular, renal, and mortality outcomes, irrespective of baseline use of metformin [ 16 ]. The finding that SGLT2 inhibitors are associated with a reduced risk of cardiovascular death or hospitalization for HF even in metformin-naïve patients with T2D at high cardiovascular risk or with CVD [ 17 ] supports the updated guidelines that recommend SGLT2 inhibitors as first-line therapy in this patient population [ 1 , 2 ]. However, in such clinical settings, it remains uncertain whether SGLT2 inhibitors affect clinical parameters similarly or differently according to the use of background metformin therapy.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…A meta-analysis on SGLT2 inhibitors also showed a consistent reduction in the risk of cardiovascular, renal, and mortality outcomes, irrespective of baseline use of metformin [ 16 ]. The finding that SGLT2 inhibitors are associated with a reduced risk of cardiovascular death or hospitalization for HF even in metformin-naïve patients with T2D at high cardiovascular risk or with CVD [ 17 ] supports the updated guidelines that recommend SGLT2 inhibitors as first-line therapy in this patient population [ 1 , 2 ]. However, in such clinical settings, it remains uncertain whether SGLT2 inhibitors affect clinical parameters similarly or differently according to the use of background metformin therapy.…”
Section: Discussionmentioning
confidence: 79%
“…To date, several secondary observations and meta-analyses using data obtained from CVOTs on newer glucose-lowering agents have been conducted to assess the influence of baseline metformin therapy on the effect of these agents on cardiovascular outcomes [ 13 17 ]. A secondary analysis of the EMPA-REG OUTCOME (Empagliflozin Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Patients-Removing Excess Glucose) trial showed that the cardiovascular benefits of empagliflozin treatment in patients with T2D and CVD were unaffected by the use of baseline glucose-lowering agents, including metformin [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of trials have shown significant reductions in major CV events after treatment with GLP-1 receptor agonists [ 152 , 153 , 154 , 155 ]. These results were further supported by a recent meta-analysis, in which GLP-1 receptor agonist treatment reduced major adverse CV events (MACE) by 12% [ 156 ].…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…This meta-analysis was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines for reporting systematic reviews [21].…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%